Investigation of glenoid fossa roof thickness in patients with and without TMJ disorders in a Turkish Subpopulation - Oguzhan Altun; Elif Sobi; Numan Dedeoglu (Medicine Science)
The aim of this study was to evaluate the minimum thickness of the glenoid fossa (GFMT), the discontinuity of the roof of the glenoid fossa, and degenerative bone changes (DBC) using cone-beam computed tomography (CBCT), and to compare these findings between the patients with temporomandibular joint dysfunction (TMD) and patients witout TMD. CBCT images of 72 patients with TMD and 72 patients with non-TMD were evaluated for DBC and GMFC in the TMJ. The obtained data were compared between TMD group and non-TMD group, between DBC group and non-DBC group and between genders. Chi-square, fisher exact, and Mann-Whitney U tests were used to compare the data. The frequency of DBC was statistically different between the TMD group (79.2%) and non-TMD group (55.6%) (p=0.000). There was no statistical difference in the GFMT between in the TMD group (0.873 mm) and non-TMD group (0.853 mm). GFMT was statistically higher in DBC group (0.92 mm) compared to non-DBC group (0.738 mm) (p0.05). The mean GFMT was found to be statistically higher in males than in females (p [Med-Science 2024; 13(4.000): 769-74]